Human Development Index and Halal Tourism Performance: Case Study of The Country with The Lowest Safety for Muslim Tourists - Lubis, Rukiah; Rusydiana, Aam; Nasirin, Wanda Khairun; Kartikawati, Dwi Ratna (Univeristas Islam Bandung, 2023)
The purpose of this study is to see the cause and effect between the Human Development Index and the Global Muslim Travel Index. This research was conducted using quantitative research methods for a dataset of five countries with low security levels. The study was analyzed by the Bayesian Vector Autoregression Panel using Eviews 10. The findings reveal that there is no interaction and contribution between the Human Development Index and the Global Muslim Travel Index in countries with weak security levels for Muslim tourists. However, according to the PBVAR estimate, the Human Development Index affects the Global Muslim Travel Index, as well as the Global Muslim Travel Index affects the Human Development Index. Then the results of the IRF test explained that the Human Development Index and the Global Muslim Travel Index had a stable response in the second period. Finally, the decomposition analysis explains that the Human Development Index and the Global Muslim Travel Index have their respective roles from the first period to the tenth period. Through this research, it is hoped that the relevant state governments can mix policies and anticipate shocks that occur. Therefore, the researcher proposes to increase security for Muslim tourists visiting their country and implement various facilities that support comfort for Muslim tourists.